2300V Reverse Breakdown Voltage Ga2O3 Schottky Rectifiers - Yang, Jiancheng; Ren, F.; Tadjer, Marko; Pearton, S. J.; Kuramata, A. (ECS journal of solid state science and technology, 2018)
We report field-plated Schottky rectifiers of various dimensions (circular geometry with diameter 50-200 μm and square diodes with areas 4 × 10−3-10−2 cm2) fabricated on thick (20μm), lightly doped (n = 2.10 × 1015 cm −3) β-Ga2O3 epitaxial layers grown by Hydride Vapor Phase Epitaxy on conducting (n = 3.6 × 1018 cm−3) substrates grown by Edge-Defined, Film-Fed growth. The maximum reverse breakdown voltage (VB) was 2300V for a 150 μm diameter device (area = 1.77 × 10−4 cm−2), corresponding to a breakdown field of 1.15 MV.cm−1. The reverse current was only 15.6 μA at this voltage. This breakdown voltage is highest reported for Ga2O3 rectifiers. The on-state resistance (RON) for these devices was 0.25 Ω.cm2, leading to a figure of merit (VB2/RON) of 21.2 MW.cm−2. The Schottky barrier height of the Ni was 1.03 eV, with an ideality factor of 1.1 and a Richardson's constant of 43.35 A.cm−2.K−2 obtained from the temperature dependence of the forward current density. The breakdown voltages for the different size devices ranged from 1400-2300V, with a general, but not linear trend of decreasing breakdown voltage for larger area rectifiers. The reverse recovery time was ∼22 ns for switching from +2 V to −2 V.